2010
DOI: 10.3390/nu2020128
|View full text |Cite
|
Sign up to set email alerts
|

Oiling the Brain: A Review of Randomized Controlled Trials of Omega-3 Fatty Acids in Psychopathology across the Lifespan

Abstract: Around one in four people suffer from mental illness at some stage in their lifetime. There is increasing awareness of the importance of nutrition, particularly omega-3 polyunsaturated fatty acids (n-3 PUFA), for optimal brain development and function. Hence in recent decades, researchers have explored effects of n-3 PUFA on mental health problems over the lifespan, from developmental disorders in childhood, to depression, aggression, and schizophrenia in adulthood, and cognitive decline, dementia and Alzheime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
94
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 172 publications
(203 reference statements)
0
94
0
5
Order By: Relevance
“…As outlined earlier, a number of mechanisms have been identified for the roles of n-3 LCPUFA in the brain [18,21] that include potentially vascular mechanisms which may underlie both cardiovascular and mental health [19]. Further supportive of this, Canadian researchers investigated n-3 PUFA levels in people who had suffered an acute myocardial infarction and found that those who suffered major depression had notably lower n-3 PUFA levels and omega-3 index (4.46%) than those without depression (5.05%) [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As outlined earlier, a number of mechanisms have been identified for the roles of n-3 LCPUFA in the brain [18,21] that include potentially vascular mechanisms which may underlie both cardiovascular and mental health [19]. Further supportive of this, Canadian researchers investigated n-3 PUFA levels in people who had suffered an acute myocardial infarction and found that those who suffered major depression had notably lower n-3 PUFA levels and omega-3 index (4.46%) than those without depression (5.05%) [46].…”
Section: Discussionmentioning
confidence: 99%
“…The role of EPA and DHA in improving endothelial function via production of antiinflammatory eicosanoids, reducing adhesion of substances to the endothelial wall and influence on nitric oxide production (and therefore vasodilation and blood flow) may contribute to common underlying mechanisms for their protective role in cardiovascular and mental health [19]. A growing body of work has investigated the role of n-3 LCPUFAs in mental health with indications of benefit across the lifespan including developmental disorders, depression, schizophrenia and cognitive decline [20,21]. Following the latter studies reviewed, a robust multi-centre trial reported that n-3 LCPUFA supplementation for 12 weeks was able to significantly reduce transition to psychosis at 12 month follow-up compared to placebo in young people at high risk for psychosis [22].…”
Section: Introductionmentioning
confidence: 99%
“…Fish is rich in n-3 long chain polyunsaturated fatty acids (n-3 LCPUFAs) and other important nutrients, such as vitamin D, selenium, iodine and high-quality protein [11,12]. Especially the n-3 LCPUFAs have received considerable interest, and there is growing evidence that suboptimal intakes of n-3 LCPUFAs may be associated with mental health over the lifespan [13,14]. The most prominent findings have been revealed for depression [15], but there is also some support for an effect of n-3 LCPUFAs in subgroups of children with attention-deficit hyperactivity disorder (ADHD) [16].…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent findings have been revealed for depression [15], but there is also some support for an effect of n-3 LCPUFAs in subgroups of children with attention-deficit hyperactivity disorder (ADHD) [16]. Still, findings from randomized controlled trials (RCT) with clinical populations remain inconclusive [14] and no benefits on mental health were seen in a sample of typically developing children after supplementation with n-3 LCPUFAs for 16 weeks [17]. However, long-term effects were found for both externalizing and internalizing problems, after 6 months supplementation with n-3 LCPUFAs in a community-residing sample of children (8–16 y), suggesting a delayed effect of n-3 LCPUFAs [18].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, considerable research has in recent decades investigated benefits of omega-3 polyunsaturated fatty acids (n-3 PUFAs) for mental health across the lifespan including attention deficit hyperactivity disorder (ADHD) and learning difficulties, uni-and bipolar depression, schizophrenia and mild cognitive impairment [15,16]. However, a range of nutrients and other food components (e.g.…”
Section: Introductionmentioning
confidence: 99%